Diagnosis and medical management of oesophageal penetration in an abused dog - Mazda, Delna; Ahamad Azahari, Ikhwan Saufi; Aslam, Muhammad Waseem; Megat Abdul Rani, Puteri Azaziah; Lau, Seng Fong (Nexus Academic Publishers, 2021)
An adult male local breed dog was referred with the signs of haematemesis, haemoptysis and swelling at the ventral neck region. History revealed removal of a wooden stick from the oral cavity a day before presentation. Physical examination revealed a sublingual hematoma. Complete blood count revealed marked neutrophilic leucocytosis with left shift and low thrombocyte count. Serum biochemistry profile showed marked hyperglobulinaemia, elevated alanine aminotransferase and alkaline phosphatase. Radiographic examination revealed presence of a round soft tissue or fluid opacity structure just ventral to the larynx and multiple small rounded air opacities coalescing to linear gas opacities in bilateral fascial planes of the neck. Computed tomography (CT) scan revealed multiple small rounded air densities coalescing to form linear gas–attenuating density in the periphery of oesophagus, indicating cervical soft tissues emphysema. The dog was managed medically and regained appetite four days after hospitalisation. The dog was discharged after five days of hospitalization. No recurrence of clinical signs was reported.